Hypertensive Patients With Reduced Blood Pressure Still Have Hypertension: The Role of the Hypertension Specialist - Giles, Thomas D. (J Clin Hypertens (Greenwich), 2007)
“There is no good theory of disease which does not at once suggest a cure.”—Ralph Waldo Emerson